Caracterização funcional da proteína Triose fosfato isomerase de Paracoccidioides brasiliensis como potencial adesina - Pereira, Luiz Augusto (2008)
Paracoccidioides brasiliensis, an important human pathogen causative of paracoccidioidomycosis (PCM), a systemic mycosis with broad distribution in Latin America. Adhesion to and invasion of host cells are essential steps involved in the infection and dissemination of pathogens. Furthermore, pathogens use their surface molecules to bind to host extracellular matrix components to establish infection. An adhesin of P. brasiliensiswas isolated from two dimensional electrophoresis and characterized. Peptides obtained by partial sequencing of the isolated protein, which presenteda molecular mass of 29 kDa and pI 5.8, were subjected to sequence analysis of their amino acids, that revealed strong homology to triose phosphate isomerase (TPI) from several sources. The complete cDNA and gene encoding TPI of P. brasiliensis (PbTPI) were characterized and both contained an open reading frame predicted to encode a 249 amino acid protein that presented all the peptides characterized in the native PbTPI. The complete coding PbTPI cDNA was cloned and over expressed in Escherichia coli host. The purified recombinant TPI was used to produce polyclonal antibody in rabbit. By immunoelectron microscopy and Western blot analysis, TPI was detected in the cell wall and the cytoplasm of the yeast phase of P. brasiliensis. The expression of PbTPI was analyzed in transition from mycelia to yeast phase. The native PbTPI is preferentially expressed in the yeast parasitic phase of P. brasiliensis. The recombinant PbTPI was found to bind to laminin and fibronectin in ligand far-Western blot assays. TPI binds preferentially to laminin, as determined by peptide inhibition assays. Of special note, the treatment of P. brasiliensisyeast cells with anti-PbTPI polyclonal antibody and the incubation of pneumocytes and VERO cells with the recombinant protein promoted inhibition of adherence and internalization of P. brasiliensisto those in vitrocultured cells. These observations indicate that TPI could be contribute to the adhesion of the microorganism to host tissues and to the dissemination of infection.